Examining the Impact of First Nations Status on the Relationship Between Diabetes and Cancer (Mary Ann Liebert, 2020)
Purpose: This population-based study examined the relationship between diabetes and cancer and determined if this relationship was influenced by First Nations (FN) status. Methods: In a matched case?cohort study, individuals 30?74 years of age diagnosed with diabetes during 1984?2008 in the province of Manitoba, Canada, with no cancer diagnosis before their diabetes diagnosis were matched to one diabetes-free control by age, sex, FN status, and residence. Flexible competing risk and Royston?Parmar regression models were used to compare cancer rates. Results: Overall, 72,715 individuals diagnosed with diabetes were matched to controls. In all age groups, diabetes was related to an increased risk of cancer. The relationship between diabetes and any type of cancer was not influenced by FN status (i.e., there was no interaction between the diagnosis of diabetes and people's FN status for any age group). The only significant interaction between diabetes and FN status was for kidney cancer for individuals 60?74 years of age; diabetes increased the risk of kidney cancer for all other Manitobans (AOMs) but not for FN. Conclusions: Diabetes increased the risk of cancer. The association was not modified by FN status except for kidney cancer where diabetes increased the risk for AOMs but not for FN.